The Securitization of Foreign Aid - Brown, Stephen; Grävingholt, Jörn (Rethinking International Development series, 2016)
Security concerns increasingly influence foreign aid: how Western countries give aid, to whom and why. With contributions from experts in the field, this book examines the impact of security issues on six of the world's largest aid donors, as well as on key crosscutting issues such as gender equality and climate change.